Upaya Guru Fiqih dalam Meningkatkan Kesadaran Beribadah Siswa di MTSS Arafah Binjai - Rahayu, Widia; A, Arlina; Salim, Nasrun (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to gain a deep understanding of the efforts made by Fiqh teachers in increasing students' awareness of worship at MTs Arafah Binjai. This effort is very important because awareness of worship is one of the fundamental aspects in the formation of students' character and personality, which not only affects their personal lives, but also their social interactions with the community. The method used in this study is a qualitative method with a phenomenological approach. The phenomenological approach was chosen because it aims to understand and explore individual experiences and perspectives in depth related to the phenomenon being studied. Data collection was carried out through three main techniques, namely observation, interviews, and documentation. The results of the study showed that the efforts of fiqh teachers in increasing students' awareness of worship at MTs Arafah Binjai included the implementation of student control books, role models, habituation, punishment, and reward. The control book is used to monitor the development of students' worship and build cooperation with parents. Modeling is done by giving direct examples of worship and good attitudes. Habits include congregational prayer, memorizing the Qur'an, giving alms, and tahfiz. Punishment is given for violations, while rewards in the form of praise and gifts are given to disciplined students. Inhibiting factors found include peer interference during prayer or tahfiz, lack of parental understanding of religious education, and family economic conditions that make some students work after school, so they often miss worship.